2006
DOI: 10.2478/s11756-006-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of Oncorhynchus mykiss during embryogenesis and other developmental stages

Abstract: Fatty acid compositions of rainbow trout Oncorhynchus mykiss (Walbaum, 1792) was determined during embryogenesis, yolk-sac fry, swim up fry and fry stages. Embryonic and yolk-sac development of fertilized eggs were followed until fry weighed 25 g and samples were taken from each stage to analyse fatty acid composition. Analyses of fatty acid composition were performed by gas chromatography mass spectrometry. Throughout all the developmental stages of O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
4
0
2
Order By: Relevance
“…These results indicating LC‐PUFA are oxidized more quickly than other FA classes during embryogenesis in this species. In contrast, Zengin and Akpinar () reported that SFA is oxidized more quickly than PUFA during embryogenesis of O. mykiss . These discrepancies between our study and findings of the above‐mentioned research might be related to differences in water temperature, brood stocks nutritional history, hatchery condition, or differences in subspecies.…”
Section: Discussionmentioning
confidence: 90%
“…These results indicating LC‐PUFA are oxidized more quickly than other FA classes during embryogenesis in this species. In contrast, Zengin and Akpinar () reported that SFA is oxidized more quickly than PUFA during embryogenesis of O. mykiss . These discrepancies between our study and findings of the above‐mentioned research might be related to differences in water temperature, brood stocks nutritional history, hatchery condition, or differences in subspecies.…”
Section: Discussionmentioning
confidence: 90%
“…This FA was bioconcentrated in liver tissue relative to the diet and thus should have been available for vitellogenesis. Fernández-Palacios et al (1995) noted that EPA concentration was more diet dependent than DHA in eggs of S. aurata, and other authors have noted that DHA is the most highly conserved q-3 LC-PUFA in fishes (Zengin and Akpinar 2006;Sewall and Rodgveller 2009;Tocher 2010). Additionally, Fuiman and Ojanguren (2011) found that only ARA and DHA were significantly correlated with larval quality.…”
Section: Discussionmentioning
confidence: 86%
“…Para estos ácidos en particular, o bien no se registran cambios significativos en cantidad a través del desarrollo hasta la etapa de alevinos comiendo (24), o tienden a permanecer en cantidades relativamente estables durante el mismo periodo (28). Los PUFA de contenido bajo (< 2,5%) fueron C18:3n-6, C18:3n-3, C20:2, C20:3n-6, C20:3n-3 y C22:5n-3.…”
Section: Discussionunclassified
“…Halüloúlu et ál. (24) coinciden en la interpretación aun cuando la variación que detectan particularmente para el C16, significativamente creciente a través del tiempo, no es consecuente con la afirmación; una tendencia similar, pero no significativa, registran Zengin y Akpinar (28). Por el contrario, conforme avanza el desarrollo embrionario la disminución en el contenido del ácido oleico es evidente, lo que confirma su importante consumo en estas etapas (24).…”
Section: Discussionunclassified